Ethical decision-making of tax accountants: examining the relative effect of religiosity, re-enforced tax ethics education and professional experience - Holy Kwabla Kportorgbi; Teddy Ossei Kwakye; Francis Aboagye-Otchere (Cogent Business & Management, 2022)
This paper investigates the relative effect of re-enforced tax ethics education (RTEE), religious commitment and professional experience on ethical decision-making (EDM). Survey data from 356 tax accountants were analysed using the partial least square structural equation modelling technique. The study found that intra-religious commitment predicts EDM, but inter-personal religious commitment does not predict EDM. Further, all three examined variables concurrently influence EDM, but RTEE is the most influential EDM variable. The findings of this study should energise tax practice organisations to re-enforce tax ethics education among their officers and guide the assignment of officers to ethically sensitive tax engagements. The paper contributes to Kant's theory of morality.
Keywords: 650; Ethical decision-making; professional experience; re-enforced tax ethics education; religious commitment; tax ethics